Autoradiography system with phosphor powder (ZnS:Ag) for imaging radioisotope dynamics in a living plant. (15th October 2021) - Kurita, Keisuke; Sakai, Takuro; Suzui, Nobuo; Yin, Yong-Gen; Sugita, Ryohei; Kobayashi, Natsuko I.; Tanoi, Keitaro; Kawachi, Naoki
Abstract: Radioisotope tracer imaging is useful for studying plant physiological phenomena. In this study, we developed an autoradiography system with phosphor powder (ZnS:Ag), "Live-autoradiography", for imaging radioisotope dynamics in a living plant. This system visualizes the element migration and accumulation in intact plants continuously under a light environment. An imaging test was performed on point sources of 137 Cs, with radioactivity of 10–100 kBq of being observed; this indicates satisfactory system linearity between the image intensity and the radioactivity of 137 Cs. Moreover, dynamics imaging of 137 Cs was performed on an intact soybean plant for four days. The serial images indicated 137 Cs accumulation in the node, vein, and growing point of the plant. The developed system can be used for studying plant physiological phenomena and can be employed for the quantitative measurement of radionuclides.